To stay or to move? Investigation on residents' migration intention under frequent secondary disasters in Wenchuan earthquake-stricken area - Huang, Huan; Wang, Fan; Xiao, Yi; Li, Yuan; Zhou, Hui-Ling; Chen, Jing (Frontiers in Public Health, 2022)
The deterioration of the living environment caused by the earthquake is the main migration motivation of residents in the area of the secondary earthquake disaster, and their migration intention is one of the most important factors affecting residents' happiness. This paper uses 957 effective survey samples from 12 secondary geological disaster areas after the Wenchuan earthquake to research the migration intention of residents and its influencing factors. It can be found that 45.2% of residents are willing to migrate, which means they have an instinctive reaction to profit-seeking and harm-avoiding, but it has not become a realistic choice. Investigation facts and research results show that the instinctive response of profit-seeking and harm-avoiding drives residents to make different choices. The migration of residents in areas where secondary geological disasters occur is affected not only by disasters such as debris flow, landslides, and collapse, but also by many factors such as life convenience, family income, expectations for future life, gender, education level, psychological feeling. The improved life and the optimization of the economic conditions brought about by the success of post-disaster reconstruction have made the vast majority of people more confident in the future of the disaster-stricken areas, which made most people choose to stay in those areas. This paper will provide policy suggestions for residents' migration and the reconstruction of the local social governance system in secondary geological disaster areas, which is helpful to improve ecological livability and residents' happiness in the Wenchuan earthquake-stricken area.